Development of Gold Nanoparticle-Based Plasmonic Assay Platform for Esherichia Coli Detection - Erdoğan, Duygu; Yıldız, Ümit Hakan; Arslan Yıldız, Ahu (Izmir Institute of Technology, 2017)
The traditional methods for pathogen detection have long detection time and insufficient sensitivity. Optical methods can overcome these drawbacks. There are solution based nanoparticle growth in the literature to enhance a surface sensitivity for biosensing applications. In this project, surface refractive index (RI) sensitivity was enhanced on solid support via gold growth to develop a label free, simple and costeffective methodology for bacteria screening. The gold nanoparticles (GNPs) were grown on solid support by using 20 μl of HAuCl4 / 80 μl of NH2OH at varied incubation times. Firstly, about 20 nm GNPs were synthesized and immobilized on polystyrene surfaces. Then, these GNPs were utilized as seed particles, and grown on solid support. During GNPs growth, a red shift in the plasmonic wavelength was observed. Morphological characterization showed that almost uniform gold growth could be achieved. The plasmonic platform sensitivity was validated by varied concentrations of sucrose, ethanol and BSA solutions, showing that the plasmonic platform gave a response to any small RI change. Next, two different E.coli bacterial strains’ adsorption was tested. Adsorption screenings for about 107 E.coli DH5-alpha cells/ml and 107 E.coli BL21(DE3) cells/ml in Phosphate Buffer Saline were made on growth gold surfaces. Further, E.coli BL21(DE3) containing milk and apple juice were also adsorbed on these gold surfaces with a 30 min incubation time. The results showed that these gold surfaces exhibit higher binding kinetics for bacteria. Therefore, the proposed LSPR-based label free methodology can be an alternative to the bacteria screening in water or food samples.

Bakteri tayini için kullanılan geleneksel metotlar yeterli duyarlılığa sahip değildir ve uzun tayin süreleri gerektirir. Optik metotlar bu dezavantajların üstesinden gelebilmektedir. Literatüre bakıldığında, biyoalgılama uygulamalarında, yüzey duyarlılığını arttırmak için, yüzeydeki nanopartiküllerin büyütüldüğü ve büyütmenin de yüzeyin büyüme solüsyonuna daldırılması ile yapıldığı görülmektedir. Bu projede ise, yüzeyin refraktif indeks (RI) duyarlılığının arttırılması katı yüzey üzerinde altın büyütülmesi ile sağlanmıştır ve bakteri varlığının tespiti için etiketsiz,kolay ve ucuz yeni bir metodoloji geliştirilmesi hedeflenmiştir. Altın nanopartiküller (ANP’ler) katı yüzey üzerinde 20 μl HAuCl4 / 80 μl NH2OH kullanılarak, zamana bağlı olarak büyütülmüştür. İlk olarak, 20 nm civarında ANP'ler sentezlenmiştir. Kolloidal ANP'ler polisitiren yüzeyler üzerinde immobilize edilmiş ve daha sonrasında partiküller yüzeyde büyütülmüştür. ANP’lerin büyümesi sırasında plazmonik dalga boyunda kırmızıya kayma gözlemlenmiştir. Parçacıkların katı yüzeyde neredeyse homojen immobilizasyonu ve büyümesi morfolojik karakterizasyon ile desteklenmiştir. Plazmonik platformun duyarlılığı, değişen konsantrasyonlarda sükroz, etanol ve BSA solüsyonları kullanılarak valide edilmiş ve plazmonik platformun çok küçük RI değişimlerine tepki verdiği gösterilmiştir. Son olarak, büyütülen altın parçacıkları üzerine E.coli bakterileri adsorbe edilmiştir. Yaklaşık 107 hücre/ml olan E.coli DH5-alfa ve E.coli BL21 (DE3) içeren fosfat tampon çözeltisi ve E.coli BL21(DE3) içeren süt ve elma suyu, büyütülen altın yüzey üzerinde adsorbe edilmiştir. Sonuçlar, bakterilerin artan altın boyutuna paralel olarak bağlanma kinetiğinin de arttığını göstermektedir. Önerilen LSPR-tabanlı etiketsiz metodoloji, su veya gıda örneklerindeki bakteri varlığı tespiti için alternatif olabilir.
Esherichia Coli Tayini için Altın Nanoparçacık Temelli Plazmonik Deney Platformu Geliştirme
Thesis (Master)--Izmir Institute of Technology, Biotechnology, Izmir, 2017
Full text release delayed at author's request until 2020.08.17
Includes bibliographical references (leaves: 61-67)
Text in English; Abstract: Turkish and English
Keywords: Escherichia coli; Gold nanoparticles; Pathogen detection; Bacteria screening; Plasmonic solid platform